Legal Compliance In Realizing The Attitude Of Defending The State For College Student Upn Veteran East Java - Yana Indawati; Wiwin Yulianingsih (Veteran Justice Journal, 2020)
This Research aim to find the connection between legal awareness UPN “Veteran” Jawa Timur Collegestudent with state defense attitude. Legal awareness is awareness or values contained in man about theexisting law or about laws that are expected to exist. Actually, what is emphasized is the values regardingthe function of the law and not a legal assessment of it concrete events in the community concerned. Legalawareness is very important in measuring the level of state defense attitudes. There are several indicatorsof the problem of legal awareness, namely Knowledge of legal regulations (law awareness); Knowledge ofthe contents of legal regulations (law acquaintance); Attitude towards legal regulations (legal attitude);Legal behavior patterns (legal behaviour). All indicators are related to campus regulations. Legalawareness, especially regarding student compliance in obeying the rules set by the campus. the higher thelevel of violation of campus discipline, the greater the reduction of student defending attitudes. Themethod used in this study begins with identification from various literatures related to the legal awarenessculture of students towards university regulations and policies in terms of the problems that occur and thechallenges that must be faced by the university. Then arranged in such a way as to bring up the rightproblem formulation which later can be comprehensively reviewed through field studies and directobservation, especially related to the problems taken in this study, namely the application of campusregulations to realize the attitude of defending the State in students. The research results in this study areexpected to be able to contribute to the university and the development of students who are expected tohave a spirit and attitude to defend the country.